THEOLOGICAL PERSPECTIVE OF NAHDLATUL ULAMA AND MUHAMMADIYYAH LEADERS IN FACING THE COVID-19 PANDEMIC - Ahmad Munjin Nasih; Nur Faizin; Achmad Sultoni; Titis Thoriquttyas (Al-A'raf: Jurnal Pemikiran Islam dan Filsafat)
The study on the theological perspective of religious leaders upon the Covid-19 pandemic is essential to prevent the Covid-19 transmission. This study aims to portray the theological perspective related to the destiny (al-qada' and al-qadar) of NU and Muhammadiyah leaders in Indonesia during the Covid-19 pandemic. This study is a quantitative-descriptive analysis. The data is collected through the validated and distributed semi-open questionnaires using a google form to the 175 respondents living in Java, Sumatera, Sulawesi, and Kalimantan. This study reveals that the theological perspective of Indonesia's religious leaders upon the Covid-19 pandemic followsÂ Ahlussunnah wal Jama'ah theology teaching on fate proposed by al-Ghazali, al-Baqilani, al-Juwaini, and other scholars who have similar views. Moreover, this study also affirms that NU and Muhammadiyah as moderate organizations in the aspect of destiny. Most NU and Muhammadiyah religious leaders have theological views stating that the Covid-19 pandemic is God's ordeal and test, while others believe it is God's torment and punishment.